2020
DOI: 10.2147/hiv.s252391
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dyslipidemia and Associated Factors Among Adult Patients on Antiretroviral Therapy in Armed Force Comprehensive and Specialized Hospital, Addis Ababa, Ethiopia</p>

Abstract: Background: The development of antiretroviral drugs and subsequent access to combined antiretroviral therapy contributed to the decline in morbidity and mortality rates associated with acquired immune deficiency syndrome, resulting in an increased life expectancy and improved quality of life for people living with human immunodeficiency virus. However, a cluster of metabolic derangements such as dyslipidemia is increasing, especially for those on antiretroviral therapy. Limited studies were done on the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
(64 reference statements)
2
8
0
1
Order By: Relevance
“…In the current review, BMI was found to have a positive association with dyslipidemia, which is consistent with many previous studies ( 16 , 51 , 54 , 55 ). This finding is also similar to studies conducted in Ethiopia ( 44 ), Uganda ( 56 ), and Tanzania ( 57 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current review, BMI was found to have a positive association with dyslipidemia, which is consistent with many previous studies ( 16 , 51 , 54 , 55 ). This finding is also similar to studies conducted in Ethiopia ( 44 ), Uganda ( 56 ), and Tanzania ( 57 ).…”
Section: Discussionsupporting
confidence: 92%
“…The presentation of an abnormal lipid profile is common in individuals with central obesity, anti-retroviral therapy (ART), metabolic syndrome, insulin resistance, and type 2 diabetes mellitus (DM) ( 15 ). The duration of HIV treatment, advanced age, sex, low CD4 counts, smoking, alcohol consumption, depression ( 12 , 15 , 16 ), and a diet high in saturated fat, sedentary lifestyle, and obesogenic ( 17 ) are the major risk factors of dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, recent research has suggested that dyslipidemia is one of the main risk factors contributing to the incidence and progression of atherosclerosis. Dyslipidemia is a common condition characterized by high plasma levels of cholesterol, triglycerides, or both [ 2 ] and measurement of plasma cholesterol and triglycerides levels are reliable diagnostic markers of dyslipidemia. Triglycerides and cholesterol are major lipids in the blood that are transported by lipoproteins and have different physiological functions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the incidence and severity of dyslipidemia vary based on species of drugs [11]. Studies [5,[12][13][14] to date focused on prevalence and risk assessment of lipid metabolism disorders among patients with HIV were mostly carried out in European populations, while researches in undeveloped countries were limited in undeveloped countries either by length of follow-up or small sample size. Conclusions were inconsistent across researches on account of antiretroviral drug species and intrinsic differences in study population.…”
Section: Introductionmentioning
confidence: 99%